Identifikasi Komoditas Tanaman Pangan Unggulan di Kabupaten Indramayu Melalui Analisis LQ (Location Quotient): Identification of Leading Food Crop Commodities in Indramayu Regency through LQ (Location Quotient) Analysis - Kiki Kusyaeri Hamdani; Bambang Susanto (J-Plantasimbiosa, 2021)
A leading commodity (base) has a comparative and competitive advantage over similar commodities in a region. Indramayu Regency has several superior food commodities that have great potential to be developed because they are supported by its agricultural land resources. The purpose of this research is to identify the superior food base commodities in Indramayu Regency through the LQ method. The research was conducted in Indramayu Regency in February-March 2020. The research location was determined purposively. The data collected is secondary data obtained from the Agriculture Office of Indramayu Regency, namely time series data on harvested area and food crop production in Indramayu Regency for a period of five years (2015-2019). The results showed that the distribution of the most superior food commodities in Indramayu Regency was rice. Kroya and Terisi Districts have the most superior food commodities, namely corn, soybeans, peanuts, cassava and sweet potatoes. The green bean commodity in Kedokan Bunder District has the highest LQ value> 1 among all food crops. Keywords: Basis, comparative, competitive, Indramayu, rice